An Working Parents' Needs for Early Childhood Daycare - Luh Putu Indah Budyawati; Aisyah Nur Atika; Yuniarta Syarifatul Umami; Muhammad Haidlor; Ahmad Afandi (Universitas Pendidikan Ganesha, 2023)
The family needs to require parents to work. Even mothers with young children often work in the public sector to meet their family's needs. This condition means that parents cannot care for their children during working hours, so parents need PAUD services, especially daycare or child care. This research aims to determine indicators of working parents' needs for PAUD daycare services. The type of research used in this research is survey research. The research subjects in this study were 150 working parents who entrusted their children to PAUD daycare services. The data collection method used is a survey method using a questionnaire given to respondents. Before the questionnaire is given to respondents, the questionnaire is validated first by the relevant expert. The data analysis used techniques with a Likert scale of 5. This research shows that working parents need PAUD daycare services that provide activities that can help children's development. Apart from that, parents who have a bachelor's degree and the location of the daycare and the costs incurred are also considerations for parents when entrusting their children to PAUD daycare institutions.